2016
DOI: 10.1002/cbin.10604
|View full text |Cite|
|
Sign up to set email alerts
|

Autophagy regulates the apoptosis of bone marrow‐derived mesenchymal stem cells under hypoxic condition via AMP‐activated protein kinase/mammalian target of rapamycin pathway

Abstract: Bone marrow-derived mesenchymal stem cells (BM-MSCs) have been demonstrated as an ideal autologous stem cells source for cell-based therapy for myocardial infarction (MI). However, poor viability of donor stem cells after transplantation limits their therapeutic efficiency, whereas the underlying mechanism is still poorly understood. Autophagy, a highly conserved process of cellular degradation, is required for maintaining homeostasis and normal function. Here, we investigated the potential role of autophagy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 39 publications
3
46
1
Order By: Relevance
“…Such discrepancy may be attributed to differences in hypoxic treatment protocol. Our previous studies adopted hypoxia (1% O 2 )/serum deprivation injury for 24 h to mimic ischemic microenvironment in vivo (43). However, Liu et al performed hypoxic preconditioning with 5% O 2 for 6 h (44).…”
Section: Autophagy and Apoptosis In The Bm-mscs Therapy Towards Myocamentioning
confidence: 99%
See 1 more Smart Citation
“…Such discrepancy may be attributed to differences in hypoxic treatment protocol. Our previous studies adopted hypoxia (1% O 2 )/serum deprivation injury for 24 h to mimic ischemic microenvironment in vivo (43). However, Liu et al performed hypoxic preconditioning with 5% O 2 for 6 h (44).…”
Section: Autophagy and Apoptosis In The Bm-mscs Therapy Towards Myocamentioning
confidence: 99%
“…Regulating autophagic activity may be a potential optimizing target for promoting BM-MSCs based cellular therapy for MI (43). Thus, many signaling pathways have been suggested to participate in autophagy regulation.…”
Section: Autophagy and Apoptosis In The Bm-mscs Therapy Towards Myocamentioning
confidence: 99%
“…Likewise, inducing autophagy in bone marrow-derived mesenchymal stem cells has been proposed as an approach to increase their viability upon transplantation, and hence their therapeutic efficiency in infarcted hearts [95,96]. Interestingly, the ACMs described by Omatsu et al were also reported to have numerous autophagosomes, and their ability to develop in vitro was shown to be sensitive to pharmacological inhibition of autophagy [82].…”
Section: Therapeutic Potential Of Autophagy Upon Myocardial Infarctionmentioning
confidence: 96%
“…Such discrepancy may be attributed to differences in hypoxic treatment protocol. Our previous studies adopted hypoxia (1% O 2 )/serum deprivation injury for 24h to mimic ischemic microenvironment in vivo [50]. However, Liu et.al.…”
Section: Autophagy and Apoptosis In The Bm-mscs Therapy Towards Myocamentioning
confidence: 99%
“…Regulating autophagic activity may be a potential optimizing target for promoting BM-MSCs based cellular therapy for MI [50]. Thus, many signaling pathways have been suggested to participate in autophagy regulation.…”
Section: Autophagy and Apoptosis In The Bm-mscs Therapy Towards Myocamentioning
confidence: 99%